Tinjauan Komprehensif tentang Material Berbasis Fe dalam Jurnal Thermoelectric Full-Heusler - Affan Shoffani Adam; Dianta Gintig (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Abstract: This study aims to conduct a comprehensive review of the development of iron-based thermoelectric materials with an emphasis on crystal structure, electron-phonon transport mechanisms, and efforts to improve power factor and figure of merit (ZT) values. This methods study reviews literatures discussing materials such as FeSi, FeSb₂, Heusler and Half-Heusler alloys, and Fe-based nanocomposites that have significant potential as environmentally friendly thermoelectric materials. The results of the study indicate that iron-based materials have several advantages, including abundant availability, good thermal stability, non-toxicity, and suitability for applications in the medium to high temperature range. In FeSi and FeSb₂ systems, the improvement of thermoelectric performance is strongly influenced by strong electron interactions and phonon scattering mechanisms, which can be optimized through nanostructuring, doping, and energy band engineering techniques. Meanwhile, Fe-based Full-Heusler and Half-Heusler materials show great potential for performance improvement through band engineering approaches, controlling the charge carrier concentration, and reducing the lattice thermal conductivity through phonon scattering strategies. This study also identified several key challenges still faced, such as low energy conversion efficiency, sensitivity to temperature changes, and the complexity of balancing electrical conductivity and phonon scattering processes. Overall, the results of this study confirm that Fe-based thermoelectric materials are promising candidates for supporting sustainable energy development. However, a multidisciplinary materials engineering approach is needed to achieve optimal performance for widespread industrial application. Keywords: , Iron (Fe) based, Full Heusler, Half Heusler, Figure of Merit (ZT), Thermoelectric material.